2015
DOI: 10.1177/0306312715583737
|View full text |Cite
|
Sign up to set email alerts
|

Formalization and separation: A systematic basis for interpreting approaches to summarizing science for climate policy

Abstract: In studies of environmental issues, the question of how to establish a productive interplay between science and policy is widely debated, especially in relation to climate change. The aim of this article is to advance this discussion and contribute to a better understanding of how science is summarized for policy purposes by bringing together two academic discussions that usually take place in parallel: the question of how to deal with formalization (structuring the procedures for assessing and summarizing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 48 publications
0
34
0
3
Order By: Relevance
“…It is probably impossible to understand the production of complex scoping reviews without acknowledging the role of this interplay. Following Sundqvist et al, 13 there is a point in making these informalities visible in the scientific literature and thus reducing the mismatch between formal accounts and the reality of reviewing. In a Swedish context, the division of labour between the government agencies involved in evidence-basing must not be overlooked.…”
Section: An Image Of the End Product Shaped How The Rules Were Intementioning
confidence: 99%
See 1 more Smart Citation
“…It is probably impossible to understand the production of complex scoping reviews without acknowledging the role of this interplay. Following Sundqvist et al, 13 there is a point in making these informalities visible in the scientific literature and thus reducing the mismatch between formal accounts and the reality of reviewing. In a Swedish context, the division of labour between the government agencies involved in evidence-basing must not be overlooked.…”
Section: An Image Of the End Product Shaped How The Rules Were Intementioning
confidence: 99%
“…The formal rules serve to minimize the influence of personal biases when searching, mapping, and synthesizing scientific studies . Empirical studies of the production of knowledge within STS and other fields, however, have shown that formalized methods help create a canonical view of general and objective scientific knowledge although the actual practices of science are highly particular and informal . These findings are particularly interesting in light of the increasing development towards a formalized scoping review method, which is becoming more similar to the traditional systematic review methodology within EBM.…”
Section: Introduction: Evidence‐basing Sts and The Case Of A Scopinmentioning
confidence: 99%
“…In this context, the aim of formalization was to make sure that the SES procedures are "purpose driven, robust, and deliver results" (IPBES 2014b, 2). However, this type of formalization certainly contributed to restricting the available space for bottom-up and inclusive process (see Sundqvist et al 2015).…”
Section: Phase 2: Translation Into Operative Norms and Conflictmentioning
confidence: 99%
“…In The third entry point for developing the Sundqvist et al (2015) framework was analyzing how civil society actors (like ENGOs) perform in terms of formalization and separation compared to other actors such as scientists and decision-makers. We have seen that this theoretical framework also can be useful for studying other actors and their knowledge production aimed at policymaking.…”
Section: Cherry-picking Rainforestsmentioning
confidence: 99%
“…We have seen that this theoretical framework also can be useful for studying other actors and their knowledge production aimed at policymaking. Yet it has proved necessary to introduce nuances into certain areas of Sundqvist et al's (2015) framework. For example, whether and how the letter is a formalized source of knowledge is a point of contention: It is weakly formalized as such, yet it depends on highly formalized sources (like the IPCC and the Stern report)…”
Section: Cherry-picking Rainforestsmentioning
confidence: 99%